Selection of superior trees of Pinus pseudostrobus, highly resin producing in Michoacan - Muñoz-Flores, Hipólito Jesús; Sáenz-Reyes, J. Trinidad; Barrera-Ramírez, Rubén; Gómez-Cárdenas, Martín; Hernández-Ramos, Jonathan (Ecosistemas y Recursos Agropecuarios, 2022)
Michoacán is the main producer of pine resin, with little more than 90% of the national production, but at present, the forests have not received treatments that guarantee sustainable use, greater productivity,and quality of the resin, through genetic improvement. The objective was to select highly resin-producing trees of Pinus pseudostrobus, with the linear regression selection method in three altitudinal gradients in natural stands of the Nuevo San Juan Parangaricutiro Indigenous Community, Michoacán. Statistical analysis showed no differences in resin production between gradients and that resin production is highly correlated with age and normal diameter. Of the preselected trees, 9 trees were superior, with resin production of 6.1 to 7.3 kg tree−1 9 months−1. These trees can be included in commercial forest plantations or seed orchards for resin production.
Keywords: Genetic improvement, linear regression, resination, altitudinal gradients, San Juan Nuevo.